Fairly rare small-diameter hepatocellular carcinoma with right adrenal gland metastasis having an inferior vena cava tumor thrombus: a case report - Takamichi Igarashi; Norifumi Harimoto; Nozomi Matsumura; Masaya Sugiyama; Kenichiro Araki; Takehiko Yokobori; Takashi Kosone; Hitoshi Takagi; Shinichi Aishima; Hideaki Yokoo; Ken Shirabe (Surgical Case Reports)
Abstract Background Hepatocellular carcinoma (HCC) may lead to extrahepatic metastasis (EHM). Most patients with EHM had either intrahepatic stage III or IVA tumor at the site of metastases. Herein, we present the case of a fairly rare 1.5-cm small-diameter HCC with right adrenal gland tumor having an inferior vena cava (IVC) tumor thrombus. Case presentation A 75-year-old man had a 1.5-cm hepatocellular carcinoma (HCC) in segment 8 of the liver and a 3.0-cm right adrenal gland tumor with inferior vena cava (IVC) tumor thrombus. He underwent partial hepatectomy, right adrenalectomy, and IVC tumor thrombectomy. Tumor resection was successful, but the tumor progressed rapidly, and the patient died 8 months after the operation. Immunohistochemical staining revealed that both HCC cells and adrenal tumor cells were positive for HCC markers Glypican-3 and alpha-fetoprotein. In terms of adrenal carcinoma markers vimentin and Melan-A, vimentin was negative in the HCC and adrenal tumor, and Melan-A was negative in the HCC. In adrenal tumor, slight positivity of Melan-A was observed, but the intensity of staining was clearly weak compared with that in normal adrenal glands. CD133, one of the stem cell markers, was positive in both HCC and adrenal tumor cells. Next-generation amplicon sequencing analyses were performed using DNA derived from the HCC, adrenal tumor, and normal liver tissue. After exome data analyses for representative HCC-related genes as TERT, CTNNB1, TP53, and ARID2, TP53 mutation (exon3: c.G351 T: p.R117S) was found in both HCC cells and adrenal tumor cells. Conversely, no significant mutations in other genes were observed. These pathological findings and sequencing results showed that the adrenal tumor might be an adrenal metastasis of HCC in spite of small primary tumor size. Conclusions This case suggests that the right adrenal tumor was a metastasis of HCC. Immunohistochemical staining and gene mutation analyses using NGS are very useful in differentiating the tumor origin.